Morphological differentiation among isolated populations of dwarf snakehead fish, Channa gachua (Hamilton, 1822) using truss network analysis - Jearranaiprepame, Pornpimol (Acta Biologica Szegediensis, 2017)
Truss-network analysis was applied to examine morphological differences among distinct populations of Channa gachua (Hamilton 1822). Ninety-eight fish individuals were collected from three-isolated habitats in north-eastern Thailand. Twenty-six truss variables were measured and then subjected to Burnaby’s size adjustment for removing size-dependent effect. The transformed data were processed for univariate and multivariate statistical analyses. The multivariate ANCOVA showed highly significant differences between populations (Pillai’s trace = 1.561, F = 10.102, p < 0.0001). The univariate ANCOVA presented the significant differences between 20 out of 26 truss variables (p < 0.05) representing morphological characters of head, trunk and caudal peduncle areas. The variability in body shape among three populations obviously showed by the first three components of PCA accounting for 49.98% of total variances. In addition, five variables from head area and three variables from body were selected to stepwise discriminant analysis, representing the first two discriminant functions (DF1 and DF2) accounted for 72.95 and 27.95% of shape variability, respectively. A high rate of correct classification of C. gachua to actual sampling locations was at 93.88%. The results support the existence of local adaptation of C. gachua across the isolated geographical locations, and indicate the presence of three phenotypic stocks of C. gachua regarding their habitat locations.